Applying Six Sigma and design of experiment to improve coil manufacturing processes – a case study in KSVN - Nguyen Nhu, Phong; Dang Phi, Van Hai; Thi, Kim Thu Ta; Nhu, Tu Anh Nguyen (BOHR International Journal of Advances in Management Research, 2025)
The company under study specializes in manufacturing parts for the automotive industry. The manufacturing process of the company has the problem of high failure rates (FRs), resulting in high-quality failure costs and low profit. In this research, Six Sigma was used to solve the problem with the objective to reduce the FR. The research methodology was based on the define measure analyze improve control (DMAIC) procedure, including five steps: define, measure, analyze, improve, and control. The tools used in the steps of the DMAIC procedure include cause and effect diagrams, Pareto diagrams, and control charts. In addition, design of experiments (DOEs) was also used to optimize the process parameters. After applying Six Sigma and DOE, the FR of the coil manufacturing process reduced by nearly 50%, from 10.27 to 5.33%.